Transfer of the Dominant Virus Resistance Gene AV-1pro From Asparagus prostratus to Chromosome 2 of Garden Asparagus A. officinalis L. - Nothnagel, Thomas; König, Janine; Keilwagen, Jens; Graner, Eva-Maria; Plieske, Jörg; Budahn, Holger (Frontiers in Plant Science, 2022)
An introgression breeding programme was carried out to transfer the virus resistance gene AV-1pro from the wild species Asparagus prostratus to the garden asparagus A. officinalis. Serious crossing barriers caused by genetic distance and different ploidy level of the crossing parents have been overcome using embryo rescue for the F1, BC1 and BC2 generations. The male and female fertility was widely restored in BC2 and was shown to be comparable to the cultivated asparagus. Five AV-1 resistant diploid (2n = 2x = 20) BC2 plants were selected and reciprocally backcrossed with asparagus cultivars. Segregation analyses of fourteen seed borne BC3 progenies suggested a monogenic dominant inheritance of the AV-1 resistance. GBS analysis gave a strong hint for location of the resistance gene on asparagus chromosome 2. Using an Axiom SNP genotyping array for the analysis of three BC3 families with 10 AV-1 resistant and 10 AV-1 susceptible plants each, as well as 25 asparagus cultivars, the AV-1pro locus on chromosome 2 was further narrowed down. The SNP with the highest LOD score was converted to a KASP marker, shown to be useful for the further backcross programme and serving as starting point for the development of a diagnostic marker.